Synthesis and physical properties of poly(l‐lactic acid)‐poly(dimethyl siloxane) multiblock copolymers prepared by direct polycondensation. Issue 9 (30th November 2013) - Fukae, Ryohei; Okada, Yoshiro; Kawatsuki, Nobuhiro
ABSTRACT Multiblock copolymers consisting of poly(l‐lactic acid) and poly(dimethyl siloxane) were prepared by the polycondensation of oligo(l‐lactic acid) (OLLA) with dihydroxyl‐terminated oligo(dimethyl siloxane) and dicarboxyl‐terminated oligo(dimethyl siloxane). Copolymers with number‐average molecular weights of 18, 000−33, 000 Da and various content ratios of oligo(dimethyl siloxane) (ODMS) unit were obtained by changing the feed ratio of these oligomers. A film prepared from the copolymer with an ODMS content ratio of 0.37 exhibited two independent peaks at −107°C and 37°C in the mechanical loss tangent for temperature dependence, suggesting the formation of microphase separation between the OLLA and ODMS segments. The film had a tensile strength of 3.2 MPa and a high elongation of 132%. The film also exhibited a high strain recovery even after repeated straining. The incorporation of dimethyl siloxane units as multiblock segments was confirmed to improve the flexibility of poly(l‐lactic acid). © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40211.